Foreign investor engagement: Stock market liberalization and corporate green innovation in China - Li, Tiantian; Liu, Xiaoxue; Fan, Shuangshuang (Frontiers in Environmental Science, 2022)
To confront the growing threat of climate change and achieve carbon neutrality, green governance has come under the spotlight globally.This paper investigates the effect of stock market liberalization on corporate green innovation, aiming to explore whether foreign investor engagement contributes to the green development of Chinese enterprises. Employing a staggered DID estimation, we find that firms generate a higher level of green innovation output after they experience the liberalization, and this effect is more pronounced when foreign investors become the focal firms’ top ten shareholders. Meanwhile, foreign investors who enter China’s A-share market with the implementation of this policy are value investors, indicating that stock market liberalization can help lead firms’ investment decision more future-oriented. We also find that financing constraints play a significant role in the association between stock market liberalization and corporate green innovation. The results of heterogeneity analyses show that the positive implication of liberalization on corporate green innovation is stronger for non state-owned enterprises, firms in high-tech industries and firms in less polluted industries. Our paper provides new insights into the economic effect of foreign investor engagement in emerging capital market and the factors affecting corporate green innovation in China.